The National Referendum in the Polish Legal Tradition - Chęciński, Remigiusz; Kozłowski, Paweł (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2025)
This article provides a concise historical-legal analysis of the national referendum in the Polish constitutional tradition from 1918 to the present. It examines how successive political systems—the Second Republic, the People’s Republic of Poland and the Third Republic—shaped both the normative framework and the practical functioning of the referendum. The study shows that despite its constitutional status as an instrument of direct democracy, the referendum has been used predominantly for political or legitimising purposes, with genuine civic participation being limited in practice. Only the 1997 constitutional referendum and the 2003 EU accession referendum fulfilled a substantive democratic role. The article highlights long-term patterns of instrumentalisation and the structural barriers that have hindered the consolidation of the referendum as an authentic expression of popular sovereignty.